2014
DOI: 10.3389/fimmu.2014.00205
|View full text |Cite
|
Sign up to set email alerts
|

The Promising Potential of Menstrual Stem Cells for Antenatal Diagnosis and Cell Therapy

Abstract: Menstrual-derived stem cells (MenSCs) are a new source of mesenchymal stem cells isolated from the menstrual fluid. Currently, there is a growing interest in their clinical potential due to fact that they are multipotent, highly proliferative, and easy to obtain in a non-invasive manner. Sampling can be repeated periodically in a simplified and reproducible manner devoid of complications that no existing cell source can match. MenSCs are also free of ethical dilemmas, and display novel properties with regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 65 publications
1
85
0
4
Order By: Relevance
“…Abundant evidence shows that miRNAs are involved in the regulation of pathogenic and pathological processes of IS, such as angiogenesis, apoptosis, proliferation, haematopoiesis, metabolism, immune function and depression after stroke [31-33]. These small molecules can serve as diagnostic, prognostic and therapeutic biomarkers in various phases of IS [14].…”
Section: Discussionmentioning
confidence: 99%
“…Abundant evidence shows that miRNAs are involved in the regulation of pathogenic and pathological processes of IS, such as angiogenesis, apoptosis, proliferation, haematopoiesis, metabolism, immune function and depression after stroke [31-33]. These small molecules can serve as diagnostic, prognostic and therapeutic biomarkers in various phases of IS [14].…”
Section: Discussionmentioning
confidence: 99%
“…MenSCs are similar to mesenchymal stem cells (MSCs), which have proliferative capabilities and broad multipotency, including the ability to differentiate into cell types belonging to all three germ lineages [68]. MenSCs exhibit higher proliferation rates than bone marrow-derived MSCs and can be easily obtained without invasive procedures [911]. In particular, our and other groups have reported that MenSCs induce low-level immunogenicity in clinical studies and can be expanded through at least 20 passages without genetic abnormalities [9, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…MenSCs exhibit higher proliferation rates than bone marrow-derived MSCs and can be easily obtained without invasive procedures [911]. In particular, our and other groups have reported that MenSCs induce low-level immunogenicity in clinical studies and can be expanded through at least 20 passages without genetic abnormalities [9, 12, 13]. The therapeutic potential of MenSCs has been demonstrated in several disease models, such as Duchenne muscular dystrophy, stroke, type 1 diabetes, premature ovarian failure, and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we focused our study on menstrual stem cells (MenSCs), isolated from menstrual blood. In this context, although MenSCs have been previously reported as multipotent cells with a potent angiogenic effect [29, 30], the angiogenic response of MenSCs or its paracrine signals, specifically through exosomes, in a tumor context remains unknown.…”
Section: Introductionmentioning
confidence: 99%